Personnel Management in the 21st Century of School Administrators in the Chiang Dao Educational Quality Development Center under the Chiang Mai Primary Educational Service Area Office 3 - Khunmuang, Angkana; Yomsoongnern, Junchai; Wangcham , Sangwan; Prasomsuk, Teerapat (MCU Haripunchai Review, 2026)
This research aims to: 1) study personnel management in the 21st century of school administrators, and 2) examine approaches for developing personnel management in the 21st century of school administrators at the Chiang Dao Subdistrict Educational Quality Development Center under the Office of Chiang Mai Primary Educational Service Area 3. The research design involved a sample group consisting of school administrators and teachers, totaling 86 participants, together with 5 experts for the interview, using a questionnaire and a structured interview as research instruments, while data were analyzed through frequency, percentage, mean, and standard deviation, with a reliability coefficient of 0.97. The research findings revealed that: 1) Personnel administration in the 21st century by school administrators was found to be at a high level overall. When considering each aspect, all were rated at a high level, ranked by average score from highest to lowest as follows: Educational quality assurance School administration Professional development / Curriculum, instruction, assessment and evaluation (with equal averages) Morality, ethics, and professional code of conduct Student affairs and activities Academic leadership 2) Guidelines for developing personnel administration in the 21st century by school administrators at the Chiang Dao Subdistrict Educational Quality Development Center under the Chiang Mai Primary Educational Service Area Office 3 revealed development approaches in each area as follows: Administrators encourage teachers to gain research knowledge and integrate it into their performance agreements. Develop academic leadership to enable supervision and promotion of Active Learning. Manage schools in alignment with 21st-century learning skills. Support teachers in curriculum, instruction, and assessment consistent with learning goals. Develop teachers’ life skills such as communication, analytical thinking, and teamwork. Provide training and knowledge on quality assurance. Uphold ethical standards in line with the professional code of conduct set by the Teachers’ Council of Thailand.